Historical dictionary of Russian and Soviet cinema - Rollberg, P. (Historical dictionaries of literature and the arts., 2016)
This second edition of Historical Dictionary of Russian and Soviet Cinema contains a chronology, an introduction, and a bibliography. The dictionary section has over 600 cross-referenced entries on directors, performers, cinematographers, composers, designers, producers, and studios. This book is an excellent access point for students, researchers, and anyone wanting to know more about Russian and Soviet Cinema.